Covid-19 on online news media : a discourse analysis of Indonesian government crisis management on Kompas.com - Prayudi,; Siti Fatonah,; Jeihan Shafira, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The COVID-19 pandemic in Indonesia had attracted debate over how the Government dealt with this crisis. Since the beginning of the pandemic, the Government has denied the spread of Covid-19 in Indonesia, although several cases were found in neighbouring countries. This research aims to analyse how the Indonesian Government handles the pandemic, based on news published online. Further, the research looked at the levels of text, social cognition, and social context of the relevant news in Kompas.com. The research method used was Teun van Dijk's Critical Discourse Analysis. The research result shows that Kompas.com presented the issue succinctly and criticised how the Indonesian Government handled the pandemic. The discourse built was that the Jokowi government was not ready to deal with the pandemic. The Government tended to ignore inputs from academics, research results, and other parties. Kompas.com sought to uncover the Government's initial response to the pandemic and subsequent policies. Further, the Government issued policies that were unclear, not firm, and constantly changing. Kompas.com positioned itself as a media that always presented news objectively, intact, independent perspective, unbiased by various political, economic, and power interests. The substance of this study contributes in the form of new policy recommendations for the heads of online media news editors on how to deliver news to the public in an open, straightforward, and critical manner that prioritises social responsibility.